A comparative study for the behavior of 3D‐printed and compression molded PLA/POSS nanocomposites. Issue 16 (6th November 2020) - Meyva‐Zeybek, Yelda; Kaynak, Cevdet
Abstract: Because of the biocompatible and nontoxic character of both PLA (polylactide) and POSS (Polyhedral Oligomeric Silsesquioxane) nanoparticles, recently being a significant alternative for biomedical parts; the main purpose of this study was to investigate performance of the 3D‐printed PLA/POSS nanocomposites with respect to the compression molded PLA/POSS specimens. Due to the higher uniformity and higher homogeneity in the distribution of POSS nanoparticles in each PLA matrix layer, mechanical tests (tensile, flexural, and toughness) revealed that the improvements in the strength, elastic modulus and fracture toughness values of the 3D‐printed specimens were much higher compared to their compression molded counterparts, the benefits starting from 13% increasing up to 78%. It was also observed that there was almost no deterioration in the physical structure and mechanical properties of the 3D‐printed specimens, even after keeping them 120 days at 37°C in a physiological solution prepared by using the standard PBS (phosphate buffered saline) tablet. Abstract :